2012
DOI: 10.22358/jafs/66148/2012
|View full text |Cite
|
Sign up to set email alerts
|

Comparative <i>in vitro</i> evaluation of forage legumes (prosopis, acacia, atriplex, and leucaena) on ruminal fermentation and methanogenesis

Abstract: Two experiments in vitro were conducted to evaluate four Egyptian forage legume browses, i.e., leaves of prosopis (Prosopis juliflora), acacia (Acacia saligna), atriplex (Atriplex halimus), and leucaena (Leucaena leucocephala), in comparison with Tifton (Cynodon sp.) grass hay for their gas production, methanogenic potential, and ruminal fermentation using a semi-automatic system for gas production (first experiment) and for ruminal and post ruminal protein degradability (second experiment). Acacia and leucaen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
58
2
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 23 publications
11
58
2
7
Order By: Relevance
“…On the other hand, tannins supplemented at a low dose to the diet may exert beneficial effects on ruminants such as improvement of feed palatability, protection of dietary protein from degradation in rumen and reduction of ruminal methanogenesis (Soltan et al, 2012). Due to different chemical structures and various biological activities, tannins are divided into two types -condensed and hydrolysable (Schofield et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, tannins supplemented at a low dose to the diet may exert beneficial effects on ruminants such as improvement of feed palatability, protection of dietary protein from degradation in rumen and reduction of ruminal methanogenesis (Soltan et al, 2012). Due to different chemical structures and various biological activities, tannins are divided into two types -condensed and hydrolysable (Schofield et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Botanically, LL belongs to the Mimosaceae family and it may grow upto 7-18 metres. LL leaves have also been shown as potential ruminants diets in terms of metabolic protein supply due to high protein content SOLTAN et al, 2012) and LL has been shown anti-methanogenic properties under in vitro and in vivo studies 2013 Schinus molle is a tree which belongs to the Anacardiaceae family. The plant occurring has been reported from Minas Gerais to Rio Grande do Sul especially southern states of Brazil.…”
Section: Brazilian Tropical Plants Tested For Methane Mitigationmentioning
confidence: 99%
“…LL leaves contains high level of protein (which can able to replace soyabean meal in ruminants diets) and it also contains tannins (it could reduce CH4 production). However, several studies reported that LL can be to improve ruminal fermentation in terms of metabolic protein supply due to its high protein content SOLTAN et al, 2012). Similiarly, LL has been shown anti-methanogenic properties in vitro and in vivo 2013).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations